2020
DOI: 10.21203/rs.3.rs-32914/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing oral microbiota composition and functionality associated with heavy cigarette smoking.

Abstract: Background: Heavy tobacco smoking, a hallmark feature of lung cancer, is drastically predominant in Middle Eastern populations. The precise links between nicotine dependence and the functional contribution of the oral microbiota remain unknown in these populations.Methods: We evaluated the composition and functional capabilities of oral microbiota with relation to cigarette smoking in 105 adults through shotgun metagenomics using buccal swabs. Results: The oral microbiota composition in our study subjects was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a previous study, the bacterial composition of seven different surface samples in the oral cavity was evaluated; similar microbial communities were observed in the buccal mucosa, gingiva, and hard palate; however, different microbial communities were observed in the saliva, tongue, tonsils, throat, and above and below the gingiva [22] . Mohammad et al [10] conducted 16S rRNA sequencing using oropharyngeal swab samples and reported that the oral microbiota composition is primarily represented by the phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria in smokers. Furthermore, they identi ed the genera Prevotella and Veillonella [10] .…”
Section: Composition Of the Pharyngeal Microecological Communities In...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, the bacterial composition of seven different surface samples in the oral cavity was evaluated; similar microbial communities were observed in the buccal mucosa, gingiva, and hard palate; however, different microbial communities were observed in the saliva, tongue, tonsils, throat, and above and below the gingiva [22] . Mohammad et al [10] conducted 16S rRNA sequencing using oropharyngeal swab samples and reported that the oral microbiota composition is primarily represented by the phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria in smokers. Furthermore, they identi ed the genera Prevotella and Veillonella [10] .…”
Section: Composition Of the Pharyngeal Microecological Communities In...mentioning
confidence: 99%
“…Mohammad et al [10] conducted 16S rRNA sequencing using oropharyngeal swab samples and reported that the oral microbiota composition is primarily represented by the phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria in smokers. Furthermore, they identi ed the genera Prevotella and Veillonella [10] . These ndings are highly consistent with those of the present study; however, because the primary focus of the study was on the population in the Middle East, which exhibits obvious differences in ethnicity and dietary habits compared with our population, and different microbial gene sequencing methods were utilized, we observed variations in the classi cation at the microbial species level.…”
Section: Composition Of the Pharyngeal Microecological Communities In...mentioning
confidence: 99%
See 1 more Smart Citation